A new nonlinear model to describe the degradation law of the mechanical properties of lead‐rubber bearings under high‐speed horizontal loading. Issue 12 (23rd August 2021) - Liu, Yanhui; Zhong, Weijian; Mercan, Oya; Tan, Ping; Zhou, Fulin
Summary: In last two decades, the base isolation technology has been increasingly used around the world to mitigate the seismic response of structures. Among several different isolation devices, lead‐rubber bearings (LRBs) became a widely used option as a result of their superior performance. However, during earthquakes with long period and duration, the temperature of the lead core in LRBs increases. This reduces the characteristic strength of the core and causes the degradation of the horizontal mechanical properties of the LRBs. This paper presents a new nonlinear hysteretic model that describes the degradation law of the horizontal mechanical properties of LRBs accurately under earthquakes with long period and long duration. Press‐shear tests of a full‐scale LRB were conducted to obtain the horizontal mechanical properties under normal‐speed horizontal loading and high‐speed horizontal loading conditions. The speed and duration of these tests are adjusted to match the maximum speed and duration of loading which isolators would typically experience under earthquakes with long period and long duration. The degradation relationships for the horizontal mechanical properties of LRBs were obtained from the experimental results. The generalized Bouc–Wen model was selected to capture this degradation. By modifying the Bouc–Wen model with the introduction of new parameters and by calibrating the resulting model using the experimental data, this paper provides a new speed‐dependent nonlinear hysteretic model for LRBs. This model can describe the degradation law of the horizontal mechanical properties of LRBs accurately. This in turn will enable more accurate seismic analysis of isolated structures under long‐period and long‐duration earthquake waves.